Data Modelling To Determine Room Rate with Adaptive Network Based Fuzzy Inference System And Particle Swarm Optimization - Sulthony, Fahd; Lukmandono; Prabowo, Rony (UNIPA PRESS, 2020)
Determination of room rate in a hotel isinfluenced by two factors, namely internal andexternal. From an external perspective, PT. PIMhas eight competitor hotels that affect its roomrate. The Hotel Manager analyzes eachcompetitor's room rate changes to staycompetitive. Human analysis has severalshortcomings: subjectivity, fatigue andinconsistency. Then we need a decision supportor decision companion machine to determine theroom rate. ANFIS-PSO is a hybrid algorithmfrom the Adaptive neural network based fuzzyinference system (ANFIS) by utilizing ParticleSwarm Optimization (PSO) optimization.Traditional ANFIS is Gradient Decent (GD) asan algorithm for parameter optimization (model).This often happens to be stuck to get optimallocal results, to overcome this PSO is used as asolution. The results obtained from the ANFIS- PSO training contained a difference of Rp.3173,187 or a percentage of 1.34%. From themodeling obtained applied to the hotel PT.PIM,with the result of an increase in revenue of Rp.17,493,548. The conclusion obtained is thatANFIS-PSO can help managers to determine theroom rate by modeling data obtained from theANFIS-PSO method. Suggestion for thedevelopment of this research is that ANFIS-PSOhas a complex complexity of training algorithmsbecause there is a combination of twoalgorithms, so to make it better a differentalgorithm design is needed.